PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADA NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Makanan Dan Minuman yang Terdaftar di BEI Tahun 2016-2017 - Krisna Sudjana; Agret Anggraini (Sekolah Tinggi Ilmu Ekonomi Gici, 2021)
Company value is very important because it can describe the company's performance which will later influence investors towards the company so that it can help make financial decisions in investing funds in the company. Therefore, it is necessary to conduct research to find out what factors affect the value of the company. The analysis technique used is multiple regression analysis. The results of the study partially showed that there were two variables, namely debt policy and profitability, which had a significant positive effect on the value of the company. While the other two variables, namely dividend policy and company size, show a negative effect on company value. The results of the study simultaneously show that together Dividend Policy, Debt Policy, Profitability, and Company Size affect Company Value. The predictive ability of the five variables to the Company Value is 96.9% as shown by the amount of adjusted R square of 96.9%, while the remaining 3.1% is influenced by other factors that are not included in the research model.